Using digital technology and school-based professional development to leverage interactive classroom teaching in Zambia - Hennessy, Sara; Haßler, Björn; Mwewa, G (2016)
This chapter describes a study which explored the feasibility of using information and communications technologies (ICTs) to support more interactive forms of subject teaching and learning in Sub-Saharan Africa. Specifically, we: • provided open educational resources (OER) to three ICT-and Internetequipped primary schools in Zambia, all serving disadvantaged communities; • worked with partners to identify the needs of school-based continuing professional development (CPD) adapted to the local context; • responded to those needs by designing an appropriate intervention – focusing on participatory, collaborative and interactive pedagogies supported by ICTs and OER, both within the classroom and for teacher development.
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Sub-Saharan Africa; Author:Haßler; Author:OpenDevEd; Björn-CV-OECS; C:Zambia; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:R; CT:T; F:learning; F:teaching; P:teacher education; P:teachers; Q:ICT; Q:OER; Q:digital technology; Q:interactive; Q:interactive pedagogy; Q:open educational resources; Q:primary education; R:evaluation; T:Classroom teaching; Z:ICT in education; Z:Intervention evaluation; Z:Primary education; Z:Teacher education; publicImportV1